What has sex got to do with it? The role of hormones in the transgender brain. (January 2019) - Nguyen, Hillary; Loughead, James; Lipner, Emily; Hantsoo, Liisa; Kornfield, Sara; Epperson, C.
Abstract Sex differences and hormonal effects in presumed cisgender individuals have been well-studied and support the concept of a mosaic of both male and female "characteristics" in any given brain. Gonadal steroid increases and fluctuations during peri-puberty and across the reproductive lifespan influence the brain structure and function programmed by testosterone and estradiol exposures in utero. While it is becoming increasingly common for transgender and gender non-binary individuals to block their transition to puberty and/or use gender-affirming hormone therapy (GAHT) to obtain their desired gender phenotype, little is known about the impact of these manipulations on brain structure and function. Using sex differences and the effects of reproductive hormones in cisgender individuals as the backdrop, we summarize here the existing nascent neuroimaging and behavioral literature focusing on potential brain and cognitive differences in transgender individuals at baseline and after GAHT. Research in this area has the potential to inform our understanding of the developmental origins of gender identity and sex difference in response to gonadal steroid manipulations, but care is needed in our research questions and methods to not further stigmatize sex and gender minorities.